2016
DOI: 10.1124/jpet.115.229542
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Levo-Tetrahydropalmatine and Low Dose Naltrexone: A Promising Treatment for Prevention of Cocaine Relapse

Abstract: Relapse to drug use is often cited as the major obstacle in overcoming a drug addiction. Whereas relapse can occur for a myriad of reasons, it is well established that complex neuroadaptations that occur over the course of addiction are major factors. Cocaine, as a potent dopamine transporter blocker, specifically induces alterations in the dopaminergic as well as other monoaminergic neurotransmissions, which lead to cocaine abuse and dependence. Evidence also suggests that adaptations in the endogenous opioid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…Moreover, some studies have confirmed that the pathophysiology of opioid addiction can be altered by up‐ or downregulation of endogenous opioids. The Sarah team demonstrated a strong negative correlation between plasma β‐EP and reinstatement . Our results further showed specific β‐EP‐positive cells located in the lateral ventricle wall and paraplexus.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Moreover, some studies have confirmed that the pathophysiology of opioid addiction can be altered by up‐ or downregulation of endogenous opioids. The Sarah team demonstrated a strong negative correlation between plasma β‐EP and reinstatement . Our results further showed specific β‐EP‐positive cells located in the lateral ventricle wall and paraplexus.…”
Section: Discussionsupporting
confidence: 72%
“…The Sarah team demonstrated a strong negative correlation between plasma β-EP and reinstatement. 37 Our results further showed specific β-EP-positive cells located in the lateral ventricle wall and paraplexus. Similar results from our previous work showed that ependymal cells transfected with the recombinant adenovirus Ad-NEP lined the lateral ventricle after icv injection.…”
Section: Increasing β-Ep In the Csf Alleviates Morphine-primed Relasupporting
confidence: 72%
“…Higher, sedation-inducing doses of l-THP may involve antagonism of postsynaptic D2 receptors as well as a non-dopaminergic (benzodiazepine-like) mechanisms via positive allosteric modulation of GABA-A receptors 64 . It is also noteworthy that non-sedative doses of l-THP (below 10 mg/kg in rodents) [65][66][67][68][69]77 , administered in combination with a low dose of a µ-opioid receptor antagonist naltrexone is more effective than l-THP alone in blocking cocaine-seeking by rats 70 . While the precise quantity of l-THP in the Heantos-4 formulation in relation to the threshold for inducing side-effects remains to be determined, our behavioral observation of Heantos-4-treated rats indicate that l-THP within the Heantos-4 formulation is well-tolerated, with no adverse side-effects aside from a mild state of somnolence (present study and ref.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the mechanism by which THP improves METH-induced behavioral phenotype is regulating brain-derived neurotrophic factor pathway, 5-HT neuronal activity, and dopamine D3 receptor (D 3 R) expression ( Yun, 2014 ; Liu et al, 2021b ). Meanwhile, THP combined with low-dose naltrexone (LDN) is used to treat cocaine relapse( Sushchyk et al, 2016 ). Combined treatment with THP and LDN can upregulate plasma β-endorphin and hypothalamic pro-opiomelanocortin.…”
Section: Pharmacological Activities Of Tetrahydropalmatinementioning
confidence: 99%